Incidence of hospitalisation for severe complications of influenza virus infection in Japanese patients between 2012 and 2016: a cross-sectional study using routinely collected administrative data - Yokomichi, H; Mochizuki, M; Lee, J; Kojima, R; Yokoyama, T; Yamagata, Z (BMJ Publishing Group, 2019)
Objective To calculate the incidence of hospitalisation due to acute respiratory failure, pneumonia, acute respiratory distress syndrome (ARDS), febrile seizures and encephalitis/encephalopathy among influenza-positive patients in Japan, where point-of-care tests are routinely used to diagnose influenza. Design A cross-sectional study using routinely collected data. Setting Japanese clinics and hospitals between 2012 and 2016. Participants Japanese patients aged 0–74 years diagnosed with influenza by a rapid test in employment-related health insurance records. Primary outcome measures Incidence of hospitalisation per 100 000 influenza-positive episodes. Results We included over 16 million influenza-positive episodes, 1.0% of whom were hospitalised. Of these, 3361 were acute respiratory failure, 27 253 pneumonia, 18 ARDS, 2603 febrile seizure and 159 encephalitis/encephalopathy. The percentage of hospitalisations by age was 2.96% of patients aged 0–1 years, 0.77% aged 2–5, 0.51% aged 6–12, 0.78% aged 13–18, 1.36% aged 19–44, 1.19% aged 45–64, and 2.21% aged 65–74. The incidence of hospitalisations from these five complications combined was highest in influenza-positive patients aged 0–1 years (943 per 100 000) compared with 307 in those aged 2–5 years and 271 in those aged 65–74 years. For pneumonia, the incidence was highest for influenza-positive patients aged 0–5 years and 65 years or more. There were statistically significant decreasing trends over the years in the incidence of all-cause hospitalisations, pneumonia and febrile seizures. Conclusions Japanese administrative data revealed that 1.0% of influenza-positive patients aged under 75 years were hospitalised. Male patients had a higher incidence of pulmonary complications and febrile seizures. Children aged 0–5 years and adults aged 65–74 years were at high risk of being admitted to hospital for pneumonia.